Efektifitas Pengawasan Dinas Lingkungan Hidup dan Kebersihan Kabupaten Badung dalam Pengelolaan Limbah Bahan Berbahaya dan Beracun Hotel (Studi Kasus Hotel di Kecamatan Kuta) - Setyawan, Kadek Restu Pradnya; Yudartha, I Putu Dharmanu; Yasintha, Putu Nomy (CITIZEN CHARTER, 2019)
ABSTRACT Tourism is the biggest sector of Badung's Revenue, therefore it needs to be supported by various activities, especially activities in maintaining the environment as tourism assets in order to survive in the long time. The progress of tourism in Badung Regency also has an impact on the environment, especially from the hospitality industry activities, especially in Kuta Sub-Distric. The problem behind this research is that there are still many hotels in Kuta Subdistrict that do not have space a while saving of hazardous and toxic material waste, lack of supervisory staff from the government. The results of this study illustrate that the monitoring of hazardous and toxic waste carried out has not been effective because of the three approaches to monitoring effectiveness, only the objective approach has the same perception while from the system and stakeholder approaches there are still differences in perceptions seen from the lack of supervisory staff with those supervised , a different and random place of supervision then the hotel is less comperative when it will be monitored and the different ways of stakeholders, which hotel in handling hazardous and toxic material waste. Keywords: Effectiveness, Supervision, Hazardous and Toxic Waste, Hotels